Urethral stricture and scrotal abscess: a rare case presentation of penile cancer and review of the literature. (4th December 2020) - De Rose, Aldo Franco; Ambrosini, Francesca; Tomasello, Laura; Boccardo, Francesco; Terrone, Carlo
Abstract: Penile cancer is a very rare malignancy and it is usually identified as a nodule or an ulceration. We report a case of locally advanced penile cancer presented as a urethral stricture and recurrent scrotal abscess. The patient had been treating for obstructive voiding symptoms and septic condition for 5 months. Because of persistent symptoms, a drainage of the abscess was performed and the histopathological examination showed infiltrating moderately differentiated squamous cell carcinoma of penis. He underwent a surgical Emasculation followed by the administration of a combination of chemotherapy (paclitaxel, ifosfamide, and cisplatin). We highlight the importance of including penile cancer in the differential diagnosis of scrotal abscess and urethral stricture. A multimodal approach is an effective strategy to manage the disease.